Space traffic management as a necessity for future orbital operations a French perspective. (January 2023) - Marty, Jean-Youri; Bonnal, Christophe; Faucher, Pascal; Francillout, Laurent
Abstract: As the number of artificial satellites put into orbit around Earth is growing very rapidly for scientific, commercial, defence or educational purposes, the need to take measures to improve safety of space operations and to contribute to the long-term sustainability of outer space activities are becoming more and more important. This paper provides an analysis of the main identified challenges to be addressed by space traffic management (STM) and an overview of a set of actions considered to tackle those challenges. The complementarity of political guidelines, regulation, standardization and operational capabilities is discussed, taking into account the need to combine the expected efficiency of the proposed actions with European industry competitiveness and also national and European security constraints.